2012
DOI: 10.1128/jvi.00252-12
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma-Associated Herpesvirus ORF54/dUTPase Downregulates a Ligand for the NK Activating Receptor NKp44

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) establishes long-term latent infection in humans and can cause cancers in endothelial and B cells. A functioning immune system is vital for restricting viral proliferation and preventing KSHV-dependent neoplasms. While natural killer (NK) lymphocytes are known to target virus-infected cells for destruction, their importance in the anti-KSHV immune response is not currently understood. Activating receptors on NK cells recognize ligands on target cells, including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 49 publications
2
49
0
Order By: Relevance
“…39 Saliently, MLL5 has been described as a nuclear protein, 28 whereas NKp44L is not found in the nucleus, consistently with data of Madrid and Ganem. 40 They also showed that during lytic Kaposi's sarcoma-associated herpes virus infection, NKp44L is instead mislocalized and concentrated in the nucleus, whereas its expression on the cell surface decreases, as previously shown in chronic HIV infection. 21,38 Intriguingly, no obvious transmembrane sequence or glycosylphosphatidylinositol anchor motif was deduced for the NKp44L sequence.…”
Section: Discussionmentioning
confidence: 59%
“…39 Saliently, MLL5 has been described as a nuclear protein, 28 whereas NKp44L is not found in the nucleus, consistently with data of Madrid and Ganem. 40 They also showed that during lytic Kaposi's sarcoma-associated herpes virus infection, NKp44L is instead mislocalized and concentrated in the nucleus, whereas its expression on the cell surface decreases, as previously shown in chronic HIV infection. 21,38 Intriguingly, no obvious transmembrane sequence or glycosylphosphatidylinositol anchor motif was deduced for the NKp44L sequence.…”
Section: Discussionmentioning
confidence: 59%
“…The significance of the NK cell response against herpesviruses is also reflected by the various mechanisms that these pathogens have evolved to evade or delay it (4). Indeed, for beta-and gammaherpesviruses, a variety of molecular mechanisms avoiding the NK-mediated antiviral activity have been defined (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Remarkably and paradoxically, such mechanisms have remained largely elusive for the alphaherpesviruses (17).…”
mentioning
confidence: 99%
“…Interestingly, during lytic infection, only surface levels of the NKp44 ligand are reduced as overall cellular levels are unchanged, indicating a defect in cellular trafficking (Madrid and Ganem, 2012). Also, while the NKp44 ligand is typically located outside of the nucleus, during lytic infection the ligand is found localizing to the nucleus (Madrid and Ganem, 2012). This localization is concurrent with a burst of lytic gene expression, mainly consisting of immune related genes (Madrid and Ganem, 2012).…”
Section: Notementioning
confidence: 88%
“…In the case of Kaposi's sarcoma-associated herpes virus, the extracellular ligand expression is reduced during de novo infection. Interestingly, during lytic infection, only surface levels of the NKp44 ligand are reduced as overall cellular levels are unchanged, indicating a defect in cellular trafficking (Madrid and Ganem, 2012). Also, while the NKp44 ligand is typically located outside of the nucleus, during lytic infection the ligand is found localizing to the nucleus (Madrid and Ganem, 2012).…”
Section: Notementioning
confidence: 99%
See 1 more Smart Citation